Postcolonial Pedagogy: Practices, Understandings and Experiences of Secondary Level English Teachers (SNPRC Journal, 2023)
The issue of postcolonial pedagogy is a well-established issue in the academia. With the aim of exploring the practices and understanding of postcolonial pedagogy in Nepali context at secondary level of Nepal. The current study had been conducted for enhancing the knowledge of English language teaching. The study explored the practices, understanding and experience of secondary level English teacher on postcolonial pedagogy based on the data achieved from the field. Applying the qualitative research design, the current study revealed the reality of practices of postcolonial pedagogy in Nepali context based on the purposive sampling. The study discovered that the secondary level teachers did not possess clear concepts of postcolonial pedagogy. The teachers' practiced based on Western elitism ideologies and their knowledge was found lacking on postcolonial pedagogy as they were away from the entire ethnic group, their culture. They were less aware of the sympathetic engagement of the learners missing the skills of creating a situation in the classroom and serving hegemonic modes of knowledge.